2020
DOI: 10.1109/access.2020.3002533
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Time Controllability and Set Controllability of Impulsive Probabilistic Boolean Control Networks

Abstract: This paper addresses the finite-time controllability and set controllability of impulsive probabilistic Boolean control networks (IPBCNs). Firstly, using the algebraic state space representation (ASSR) method, the transition probability matrix of IPBCNs is established. Secondly, a kind of finite step reachability matrix with probability one is constructed, based on which, several effective criteria are proposed for the finite-time controllability with probability one of IPBCNs. Thirdly, a necessary and suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In other words, this matrix should be a full rank matrix and rows should be independent of each other. As was mentioned in [35], if matrices boldAinv,i${{\bf A}_{{{inv,i}}}}$ and boldBinv,i${{{\bf B}}_{{{inv,i}}}}$ are time independent, the pair (boldAinv,i${{\bf A}_{{{inv,i}}}}$, boldBinv,i${{{\bf B}}_{{{inv,i}}}}$) is controllable. Therefore, according to Equation (8), it can be easily concluded that this system is controllable.…”
Section: Preliminaries and System Modelingmentioning
confidence: 98%
See 2 more Smart Citations
“…In other words, this matrix should be a full rank matrix and rows should be independent of each other. As was mentioned in [35], if matrices boldAinv,i${{\bf A}_{{{inv,i}}}}$ and boldBinv,i${{{\bf B}}_{{{inv,i}}}}$ are time independent, the pair (boldAinv,i${{\bf A}_{{{inv,i}}}}$, boldBinv,i${{{\bf B}}_{{{inv,i}}}}$) is controllable. Therefore, according to Equation (8), it can be easily concluded that this system is controllable.…”
Section: Preliminaries and System Modelingmentioning
confidence: 98%
“…Remark 1. (Controllability) [35]: System (8) is controllable if for any initial state x 0 and any final state x f , there exists an input sequence, which transfers x 0 to x f in a finite time interval. Otherwise, the system is uncontrollable.…”
Section: Dynamic Model Of Inverter-interfaced Dermentioning
confidence: 99%
See 1 more Smart Citation
“…Through the BNs, the macro-behavior and micro-mechanism of complex systems are combined, which not only gives us methodological enlightenment to study complex systems, but also presents a novel approach to address the complexity issues in the real world, specifically in systems biology [15,1], chemistry [12], engineering [17], social networks [31], etc. Recently, the introduction of the semi-tensor product (STP) has led to significant advancements in addressing various theoretical challenges associated with BNs, such as disturbance decoupling [3], stability and stabilization [2,32,43,29,36], reachability [45,28], controllability [30,19,35], synchronization [48], optimal control [34,39,40] and other related problems [37,7,10].…”
Section: Introductionmentioning
confidence: 99%